Survey on the use of Homeopathy among Pediatricians of the Italian Federation of Pediatric Physicians (FIMP) [Article in English and Italian] • [Indagine sull'utilizzo dell'Omeopatia tra i Pediatri della Federazione Italiana Medici Pediatri (FIMP)] - Gianfranco Trapani; Tiziana Di Giampietro; Luisella Zanino; Domenico Careddu (Hygeia Press di Corridori Marinella, 2017)
ENGLISH TEXT: The use of Complementary Alternative Medicine (CAM), and more specifically of Homeopathy, is common among the pediatric population in Italy. In order to verify the attitude of family pediatricians (pediatri di famiglia) towards the use of Homeopathy, a survey has been carried out among 5,399 (number of doctors who received the questionnaire) family pediatricians enrolled in the Italian Federation of Pediatric Physicians (Federazione Italiana Medici Pediatri, FIMP) by means of an online questionnaire. The response has been significant (1,252 questionnaires have been filled in, corresponding to 23.19% of the total submitted) and has highlighted that 29.4% of the pediatricians who took part in the survey use homeopathic medicine to cure their patients. The study has also analyzed several other parameters related to the use of Homeopathy, including age and pediatric education, most commonly treated diseases, pharmaceutical forms and possible adverse effects. ITALIAN TEXT: L'impiego delle Medicine Complementari e Alternative (Complementary Alternative Medicine, CAM), e più specificamente dell'Omeopatia, è comune tra la popolazione pediatrica in Italia. Allo scopo di verificare l'attitudine dei pediatri di famiglia nei confronti dell'utilizzo dell'Omeopatia, è stata condotta un'indagine, tramite un questionario online, tra i 5.399 (numero di medici che ha ricevuto il questionario) pediatri di famiglia appartenenti alla Federazione Italiana Medici Pediatri (FIMP). Il riscontro è stato significativo (1.252 questionari, corrispondenti al 23,19% di quelli inviati, sono stati compilati ) ed ha evidenziato che il 29,4% dei pediatri che hanno risposto all'indagine utilizza la medicina omeopatica per curare i propri pazienti. Lo studio ha anche analizzato alcuni altri parametri correlati all'impiego dell'Omeopatia, inclusi l'età e la formazione dei pediatri, le patologie più frequentemente trattate, le forme farmaceutiche utilizzate e i possibili effetti avversi.